Advanced Virtual Fitting Rooms: A Review of Artificial Intelligence and Augmented Reality Technologies - Ganguly, Phan Mahesh; Nga, Phan Thi Tu; Nguyen, Ha Huy Cuong (Journal of Research in Science and Engineering, 2026)
This paper analyzes the current state of biometric data privacy laws in the US, EU, and India, and how they affect the use of AR technologies in the retail fashion industry. One section of the paper focuses on how retail fashion stores use AI algorithms to offer enhanced interactive features in virtual try-on mirrors. Three-dimensional (3D) models are simulated in real-time using augmented reality (AR) and artificial intelligence (AI) technology in virtual changing rooms. Your business or organization can depict characteristics of any person, including gender, size, fit, and shape, using virtual dressing room systems that use three-dimensional (3D) models. In order to create a virtual fitting model using previously provided images, the system obtains information about custom body sizes. The system then displays the fitting effect after the model has tried on several different costumes. Augmented Reality Virtual Dressing room works by superimposing the model or picture of a garment or accessory within the live video feed of the customer. The customer's movements will then be tracked by the model or image of the clothing or accessory that is superimposed, giving the impression that the consumer is wearing the virtual item in the video view. Additionally, ubiquitous social networking capabilities enable sending images or videos of the customer wearing the item for prompt feedback.